The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1016/s0896-6273(00)80687-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Hippocampal Synapses to Natural Stimulation Patterns

Abstract: We have studied the synaptic responses in hippocampal slices to stimulus patterns derived from in vivo recordings of place cell firing in a behaving rodent. We find that synaptic strength is strongly modulated during the presentation of these natural stimulus trains, varying 2-fold or more because of short-term plasticity. This modulation of synaptic strength is precise and deterministic, because the pattern of synaptic response amplitudes is nearly identical from one presentation of the train to the next. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
180
4
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(203 citation statements)
references
References 44 publications
15
180
4
4
Order By: Relevance
“…The present study is the first example that targeted manipulation of biochemical signaling in axon terminals can enhance learning and synaptic plasticity in mammals. In addition, our data support the long-standing hypothesis that short-term presynaptic plasticity influences the induction of LTP (Dobrunz and Stevens, 1999). Specifically, our results demonstrate a novel cellular function of H-ras/ERK signaling: by regulating the density of docked vesicles via ERK-dependent phosphorylation of synapsin I, experience-dependent changes in the activity of presynaptic H-ras modulate the induction of longterm synaptic plasticity underlying learning through a frequencydependent facilitation of neurotransmitter release.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The present study is the first example that targeted manipulation of biochemical signaling in axon terminals can enhance learning and synaptic plasticity in mammals. In addition, our data support the long-standing hypothesis that short-term presynaptic plasticity influences the induction of LTP (Dobrunz and Stevens, 1999). Specifically, our results demonstrate a novel cellular function of H-ras/ERK signaling: by regulating the density of docked vesicles via ERK-dependent phosphorylation of synapsin I, experience-dependent changes in the activity of presynaptic H-ras modulate the induction of longterm synaptic plasticity underlying learning through a frequencydependent facilitation of neurotransmitter release.…”
Section: Discussionsupporting
confidence: 83%
“…Studies using a variety of invertebrate systems have provided compelling evidence for the involvement of presynaptic plasticity in invertebrate learning and memory (Burrell and Sahley, 2001). Additionally, computational models have suggested that shortterm presynaptic plasticity is an important mechanism for cortical processing in mammals (Tsodyks and Markram, 1997;Varela et al, 1997;Dobrunz and Stevens, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, response amplitudes to individual stimuli were similar from trial to trial. Repeated administration of either the sleep or wake stimulus protocol elicited similar responses to each repetition (data not shown), as has been described for analogous experiments using natural activity patterns examining Schaffer collateral synaptic responses (Dobrunz and Stevens, 1999).…”
Section: The Glutamate-glutamine Cycle Dynamically Regulates Ipscs Evsupporting
confidence: 66%
“…Formation of sharp-wave ripples depends on coordinated firing of CA3 neurons, orchestrated by parvalbumin-expressing fast-spiking interneurons (35). Place cells fire when an animal reaches a specific position in space, and firing of place cells in turn can induce LTP in vitro (32,36,37). How might the changes in short-term and long-term synaptic plasticity that we observe in IM-AA mice alter sharpwave ripples, place cell formation and stability, and ultimately spatial learning and memory?…”
Section: Discussionmentioning
confidence: 99%